x + 700 = 3000
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 9000 - 7000 = 2000
3000 - 2000 = 1000
8000 -8000 = 0
5000 - 1000 = 4000
6000 - 5000 = 1000
10000 - 2000 = 8000
b) 4600 - 400 = 4200
8500 - 500 = 8000
9900 - 300 = 9600
6800 - 700 = 6100
7200 - 3000 = 4200
5600 - 2000 = 3600
3800 - 3000 = 800
7400 - 400 = 7000
a)9000-7000=2000
3000-2000=1000
8000-8000=0
5000-1000=4000
6000-5000=1000
10000-2000=8000
b)4600-400=4200
8500-500=8000
9900-300=9600
6800-700=6100
7200-3000=4200
5600-2000=3600
3800-3000=800
7400-400=7000
3000 + 2 < 3200
6500 + 200 > 6621
8700 – 700 = 8000
9000 + 900 < 10 000
a) 3000 + 5000 = 8000
5000 + 5000 = 10 000
4000 + 4000 = 8000
7000 + 2000 = 9000
6000 + 1000 = 7000
2000 + 8000 = 10 000
b) 2000 + 700 = 2700
100 + 1000 = 1100
6000 + 600 = 6600
8000 + 500 = 8500
5000 + 300 = 5300
400 + 6000 = 6400
a) 3000+5000=8000
5000+5000=10000
4000+4000=8000
7000+2000=9000
6000+1000=7000
2000+8000=10000
b) 2000+700=2700
100+1000=1100
6000+600=6600
8000+500=8500
5000+300=5300
400+6000=6400
a) Mẫu: 5000 + 200 + 70 + 8 = 5278
7000 + 600 + 50 + 4 = 7654
2000 + 800 + 90 + 6 = 2896
8000 + 400 + 20 + 7 = 8427
9000 + 900 + 90 + 9 = 9999
b) Mẫu: 4000 + 20 + 1 = 4021
3000 + 60 + 8 = 3068
7000 + 200 + 5 = 7205
9000 + 50 + 6 = 9056
2000 + 100 + 3 = 2103
5000 + 7 = 5007
9000 + 9 = 9009
3000 + 300 + 3 = 3303
8000 + 700 + 5 = 8705
a) Mẫu: 5000 + 200 + 70 + 8 = 5278
7000 + 600 + 50 + 4 = 7654
2000 + 800 + 90 + 6 = 2896
8000 + 400 + 20 + 7 = 8427
9000 + 900 + 90 + 9 = 9999
b) Mẫu: 4000 + 20 + 1 = 4021
3000 + 60 + 8 = 3068
7000 + 200 + 5 = 7205
9000 + 50 + 6 = 9056
2000 + 100 + 3 = 2103
5000 + 7 = 5007
9000 + 9 = 9009
3000 + 300 + 3 = 3303
8000 + 700 + 5 = 8705
Thiếu đề : Tính f(2009)
\(F\left(x\right)=x^{98}-\left(x+1\right)x^{97}+\left(x+1\right)x^{96}+...-\left(x+1\right)x^2+\left(x+1\right)x-1\)
\(=x^{98}-x^{98}-x^{97}+x^{97}+x^{96}-x^{96}...-x^3-x^2+x^2+x-1\)
\(=x-1=2009-1=2008\)
f(x)=x99-3000.x98+3000.x97-...-3000x2+3000x-1
f(2009)=x99-(x+1).x98+(x+1).x97-...-(x+1)x2+(x+1)x-1
=x99-x99-x98+x98+x97-...-x3-x2+x2+x-1
=(x99-x99)+(-x98+x98)+(x97-x97)...+(-x2+x2)+x-1
=2009-1
=2008
đặt 3000=x+1 ta đc
F(x)=\(x^{98}-\left(x+1\right)x^{97}+\left(x+1\right)x^{96}+...-\left(x+1\right)x^2+\left(x+1\right)x-1=x^{98}-x^{98}-x^{97}+x^{97}+x^{96}-x^{96}.....-x^3-x^2+x^2+x-1=x-1=2009-1=2008\)
vậy.......
Ta có : 2999=x => x99-3000x98+3000x97-...+3000x-1
f(x) = x99 - (x+1)x98+(x+1)x97-...+(x+1)x-1
=x99-x99-x98+x98+x97-...x2+x-1=x-1=2999-1=2998
Vậy : f(2999)= 2998
x + 700 = 3000
x = 3000 - 700
x = 2300
k mik nha bn
x + 700 = 3000
x = 3000 - 700
x = 2300